2017
DOI: 10.1017/age.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Public Policies on Inducing Technological Change in Solar Energy

Abstract: Using patent statistics related to solar power on a panel of eleven countries from 1990 to 2008, we build a reduced-form model to analyze the role that public policies play in fostering innovation. We conclude that public expenditure on R&D and feed-in tariffs have a significant effect on the development of solar energy. We also find a significant effect of electricity price, attributable to rising energy prices. Using patent citations, we estimate the knowledge flows available to inventors in each country ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Across 30 articles, Popp et al (2010) and Popp (2019) found that a 10% increase in energy prices increased energy-related patenting by 3-6%-a "patenting elasticity" of 0.3-0.6 (also see Verdolini & Galeotti, 2011). For low carbon and energy efficient technologies specifically, elasticity averaged 0.86, and exceeded 1 for solar PV (Kruse &Wetzel, 2016, Vincenzi andOzabaci (2017)), as also found for vehicles (Aghion et al (2016)). Carbon prices also enhance low carbon patenting (Calel & Dechezleprêtre, 2016).…”
Section: Evidence On Market-induced Innovationmentioning
confidence: 87%
“…Across 30 articles, Popp et al (2010) and Popp (2019) found that a 10% increase in energy prices increased energy-related patenting by 3-6%-a "patenting elasticity" of 0.3-0.6 (also see Verdolini & Galeotti, 2011). For low carbon and energy efficient technologies specifically, elasticity averaged 0.86, and exceeded 1 for solar PV (Kruse &Wetzel, 2016, Vincenzi andOzabaci (2017)), as also found for vehicles (Aghion et al (2016)). Carbon prices also enhance low carbon patenting (Calel & Dechezleprêtre, 2016).…”
Section: Evidence On Market-induced Innovationmentioning
confidence: 87%
“…Such evidence has been enhanced by more recent studies reviewed in [15], who documented a (statistically significant) link between energy prices and patent filing for energy innovations. Ley et al find not only that higher energy prices increased patenting, but disproportionately enhance low-carbon patents [16], e.g., for solar PV [17] and electric vehicles [18]. Recent studies show a positive impact of carbon pricing and other environmental regulation on low-carbon innovation.…”
Section: Technology Progressmentioning
confidence: 99%
“…;Johnstone et al, (2010) ;Nicolli et Vona (2016) ainsi queVincenzi et Ozabaci (2017), obtiennent des effets positifs de ces mêmes politiques sur le solaire mais utilisent pour cela une variable plus précise comme mesure de la politique (le montant du FIT). Les résultats obtenus dépendent donc en partie de la façon dont sont définis le modèle économétrique et les variables de politiques, une plus grande précision dans la caractérisation des politiques conduisant à des résultats plus nettement favorables.De même, l'absence de précision dans la caractérisation des technologies conduit à des résultats non significatifs.…”
unclassified